Social Judgment as a Predictor of EFL Speaking Confidence at SMA Santa Maria Medan - Meikardo Samuel Prayuda (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Speaking confidence is an important affective factor in English as a Foreign Language (EFL) learning because students need confidence to answer questions, participate in group discussions, deliver presentations, and continue speaking even when they make mistakes. However, many EFL students experience social judgment in the classroom, including fear of negative evaluation, peer ridicule, classroom comparison, sensitivity to teacher correction, and self-consciousness. This study investigated the predictive effect of social judgment on EFL students’ speaking confidence at SMA Katolik Santa Maria Medan. The study employed a quantitative correlational design with simple linear regression. The participants were 36 senior high school students who learned English as a foreign language. Data were collected using two Likert-scale questionnaires: a Social Judgment Scale and a Speaking Confidence Scale, with scores ranging from 20 to 100. The data were analyzed using descriptive statistics, Pearson product-moment correlation, and simple linear regression. The findings showed that students’ social judgment was at a moderate-to-high level, with a mean score of 66.74 and a standard deviation of 8.34. Students’ speaking confidence was also at a moderate-to-high level, with a mean score of 72.33 and a standard deviation of 8.43. The Pearson correlation showed a strong negative relationship between social judgment and speaking confidence, r = -.801, p < .001. The regression analysis showed that social judgment significantly predicted speaking confidence, B = -0.81, t = -7.79, p < .001. The coefficient of determination showed that social judgment explained 64.1% of the variance in students’ speaking confidence. These findings indicate that students who experienced higher social judgment tended to have lower confidence in speaking English. The study concludes that reducing fear of negative evaluation, peer ridicule, classroom comparison, and excessive sensitivity to correction is important for strengthening students’ speaking confidence in EFL classrooms.